Dovlatov, scrittore russo a New York. Sulle manipolazioni traduttive e la censura identitaria - Salmon, Laura (L’ospite ingrato, 2025)
Dovlatov was not a dissident, nor an American writer, nor did he hate his country. His Soviet past is the main subject of his povesti, and even the pages focused on his American emigration express a critical and humorous approach which does not line with dissident ideological axioms. Dovlatov’s sense of belonging to Russian culture («I just want to be a Russian writer») is aware and explicit, and crucial to the interpretation of his work and style. The very ethical and aesthetic distance between the writer and the American sovietophobia oh his days explains some obvious manipulations of the American translation of his texts. We will see the exemplary case of chap. 13 of Naši (cfr. Ours 1989), where A. Frydman produces a surprising re-writing, erasing both the author’s ethical-identarian values and his refined Russian humor.